Gate Current in p-GaN Gate HEMTs as a Channel Temperature Sensitive Parameter: A Comparative Study between Schottky- and Ohmic-Gate GaN HEMTs - Alessandro Borghese; Alessandro Di Costanzo; Michele Riccio; Luca Maresca; Giovanni Breglio; Andrea Irace (Energies, 2021)
In this work, a comparison between the gate-driving requirements of p-GaN HEMTs with gate contact of Schottky and Ohmic type is presented. Furthermore, the presence of a gate current of different magnitude is experimentally verified for both types of devices. Successively, the possibility of using the gate current as a temperature-sensitive parameter and its monitoring during real circuit operation is proposed. The viability of monitoring the gate current without introducing additional complexity in the gate driver is examined through experimental measurements on commercially available p-GaN HEMTs.